The lesser occipital nerve visualized by high-resolution sonography—normal and initial suspect findings. (August 2015) - Platzgummer, Hannes; Moritz, Thomas; Gruber, Gerlinde Maria; Pivec, Christopher; Wöber, Christian; Bodner, Gerd; Lieba-Samal, Doris
Background: The lesser occipital nerve (LON) supplies the lateral part of the occiput and is—together with the greater occipital nerve (GON)—involved in headache pathogenesis. While the GON was described in high-resolution ultrasound (HRUS), the same does not apply to the LON. We aimed at characterizing the LON in HRUS, and present cases of suspect findings in the course of the LON identified by HRUS. Methods: The LON was examined bilaterally in eight anatomical specimens with HRUS ( n = 16). HRUS-guided ink marking and consecutive dissection was performed. Further, measurements of the LON diameter were performed in 10 healthy volunteers ( n = 20), and patient charts were reviewed to identify patients who were considered to have possible pathology of the LON. Results: The LON was identified correctly in all cadavers on both sides and all volunteers except for one side ( n = 19). The average diameter was 1.08 ± 0.30 mm. Four patients with pain within the LON territory and presumed peripheral origin of headache (defined as resolution of headache after diagnostic HRUS-guided selective blockade) were identified, and three of these showed interference of the LON with lymph nodes or an accessory muscle belly. Discussion: We confirm the possibility of visualization of the LON using HRUS. HRUS may be a helpful adjunct tool in the assessment of patients with atypical headache.